Emotion Regulation, Parasympathetic Function, and Psychological Well-Being - Brown, Ryan L.; Chen, Michelle A.; Paoletti, Jensine; Dicker, Eva E.; Wu-Chung, E. Lydia; LeRoy, Angie S.; Majd, Marzieh; Suchting, Robert; Thayer, Julian F.; Fagundes, Christopher P. (Frontiers in Psychology, 2022)
Stressful life events and their accompanying negative emotions can increase the risk of depressive symptoms, major depressive disorder, and higher levels of perceived stress. James Gross’ process model of emotion regulation can help distinguish between adaptive and maladaptive emotion regulation strategies when facing a stressful life event. Heart rate variability can serve as an index of an individual’s self-regulatory abilities and physiological responses to stressful life events, which can then help understand risk and resilience patterns that can impact how individuals adapt to stress. We expected individual differences in resting vagally-mediated heart rate variability to moderate the influence of emotion regulatory strategies in our sample of 267 adults. We found support for the hypothesis that higher vagally-mediated heart rate variability is a marker of resilience that protects against the typically adverse effects of expressive suppression when evaluating depressive symptoms and found weak support when evaluating perceived stress. There was no evidence for an interaction between cognitive reappraisal and vagally-mediated heart rate variability but there was a significant, negative association between cognitive reappraisal and both depressive symptoms and perceived stress. Increased knowledge of potentially adaptive regulatory options may help people prepare to cope with current and future stressful circumstances.